FEATURES OF USING INTERACTIVE TEACHING METHODS IN TRAINING OF FUTURE MILITARY PSYCHOLOGUSTS - Kozhedub, O.; Sokolina, O.; Syrytsya, M.; Kalyshenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The authors of the article reveal the methodological features of the use of interactive teaching methods, which are the most popular among teachers when organizing and conducting training sessions with future military psychologists. The article states that the situation of a full-scale russion invasion of the territory of Ukraine requires the teachers of a higher military educational institution to use optimal ways of their militaryprofessional training during training of future psychologists. These are the ways of interactive teaching methods. Thus, the method of analyzing a specific situation is used in cases where it is necessary to analyze and professionally assess the difficult life situation of a serviceman by future military psychologist. Application of the business game method, which simulates the professional activity of future military psychologists, gives the latter the opportunity to feel like an active actor in a real military-professional situation. The article states that the teacher’s use of the business game method in the educational process contributes to the transfer of accumulated long-term military psychological experience for future military psychologists. The authors draw the readers’ attention to the fact that the active position of future military psychologists is actualized and reveals its behavioral manifestation in the business game. Describing the features of the use of "brainstorming" as an interactive method of training future military psychologists, the authors emphasize that this method allows the search for new ways of solving military psychological problems through the generation of non-standard ideas. The author’s team emphasizes that "brainstorming" as an interactive learning method, contributes to the formation of future military psychologists’ confidence in their professional knowledge. The round table method is aimed at developing the cognitive activity of future military psychologists. It is stated, that this method forms in future military psychologists the ability to argue their professional point of view.